Rogue [videorecording (DVD)] - Bassett, M. J.; Bassett, M. J.; Bassett, M. J.; Fox, Megan, 1986-; Sutton, Jessica; Winchester, Philip, 1981- (Lionsgate, 2020)
A woman leads a team of mercenaries tasked with rescuing hostages in Africa.